2019
DOI: 10.1186/s12877-019-1105-3
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative examination of policy and structural factors driving care workers’ adverse experiences in long-term residential care facilities for older adults in Cape Town

Abstract: Background There is lack of adequate training and policy support for employed care workers (CWs) employed in the South African (SA) older persons’ sector. Existing literature neglects the influence of training and policy support on CWs’ experiences in long-term care (LTC) for older adults in residential care facilities (RCFs). We investigated the ways in which CWs’ experiences are rooted in the lack of adequate training and policy support. Methods Qualitative data was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Some caregivers reported that they were sent on training only after starting their jobs or received 'on the spot' training from other caregivers or given instruction by NGO managers on what to do. Similar to the current study, Mapira, Kelly and Geffen (2019) found that most community workers had to assume duties without having undergone the necessary training. The results of the current study are also consistent with a study by Burgdorf et al (2019:835), published in the JAMA Internal Medicine Journal, which revealed that more than three-quarters of caregivers are actively performing their caregiving roles without having undergone any training.…”
Section: Discussionsupporting
confidence: 86%
“…Some caregivers reported that they were sent on training only after starting their jobs or received 'on the spot' training from other caregivers or given instruction by NGO managers on what to do. Similar to the current study, Mapira, Kelly and Geffen (2019) found that most community workers had to assume duties without having undergone the necessary training. The results of the current study are also consistent with a study by Burgdorf et al (2019:835), published in the JAMA Internal Medicine Journal, which revealed that more than three-quarters of caregivers are actively performing their caregiving roles without having undergone any training.…”
Section: Discussionsupporting
confidence: 86%
“…A study of South African LTC workers showed that caregivers' motivation to provide quality care is hindered by role ambiguity, harsh employment conditions, negative interpersonal relationships at work, and role overload. These unfavorable conditions are created by policy de cits and a lack of structural support [ 23 ]. A study in Hangzhou, China, showed that low education level, long working hours, and low compensation of care workers were barriers to the development of LTC services [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salary, workload, and professional identity affect the job satisfaction of front-line workers [ 80 ], and consequently affect work performance. A study from South Africa showed that caregivers face poor employment conditions, negative relationships, and role overload [ 81 ]. According to research by the Social Welfare Center of the Ministry of Civil Affairs, workers providing care services are characterized by high turnover rate, high labor intensity, low wage income, low social status, and low service level [ 82 ].…”
Section: Discussionmentioning
confidence: 99%